Implementasi Pembelajaran Bermuatan Computational Thinking Pada Materi Kegunaan Uang di Kelas III Sekolah Dasar - Fauziah Mas'ula Soffa; Anisa Sifa Yuginanda; Siti Luluk Saniyati; Kintan Limiansih (Universitas Negeri Malang, 2023)
This article describes learning that contains computational thinking (CT) on the use of money material in grade III elementary schools. CT is a basic skill that involves problem formulation, problem-solving, as well as scientific reasoning. The government's policy regarding the need to integrate CT into learning is motivated by the low-quality index of Indonesian education in PISA and efforts to prepare students for 21st-century skills. The material about the use of money has a special urgency, namely instilling financial literacy which can be beneficial for the future of students. The method used is descriptive qualitative with primary data sources, namely class III students at SD Negeri Jatisawit totaling 32 students. The results of this study are that the implementation of CT-charged learning on the use of money material can bring up CT foundational aspects, namely decomposition and algorithms, and the teacher's ability to manage computational thinking-charged learning on the use of money material reaches a score of 91.6 percent or in the